Engaging, distancing and surrendering: moral legitimation of controversial organizational decisions in the media - Erkama, Niina (Journal of business ethics, 2024)
Although there is a vast body of work on legitimacy, we still have a limited understanding of the discursive aspects of moral legitimation. This is surprising considering the increase in morally laden societal discussions, for example related to understanding gender, rights and regulations during a pandemic, political scandals and ethics of global business amongst others. In particular, from an organization studies perspective, we lack knowledge on how journalists negotiate moral legitimation of controversial organizational decisions such as closures or shutdown decisions related to global industrial restructuring. Therefore, drawing on the critical discourse studies tradition, we examine the media coverage of controversial shutdowns in Finland over the past 2 decades. Our analysis suggests three moral legitimation types: moral engaging, moral distancing and moral surrendering. These types involve specific discursive moralization practices and strategies, and they each paint a different picture of the moral options, responsibility, and inevitability in these decisions. These types can be found in the same texts supporting each other, but they also help us understand how legitimation may involve a pattern where the most explicit reflections (moral engagement) are followed by more indirect (moral distancing) and less apparent but very powerful (moral surrendering) forms of legitimation. By so doing, we also offer a heuristic that can, with due caution, be used for analyzing other texts on adverse effects of globalization or events that might include moral and ideological conflicts.